2015
DOI: 10.1002/cmdc.201500153
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamamide Derivatives for Central and Peripheral Nervous System Disorders—A Review of Structure–Activity Relationships

Abstract: The cinnamamide scaffold has been incorporated in to the structure of numerous organic compounds with therapeutic potential. The scaffold enables multiple interactions, such as hydrophobic, dipolar, and hydrogen bonding, with important molecular targets. Additionally, the scaffold has multiple substitution options providing the opportunity to optimize and modify the pharmacological activity of the derivatives. In particular, cinnamamide derivatives have exhibited therapeutic potential in animal models of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 145 publications
(470 reference statements)
0
28
0
1
Order By: Relevance
“…Zorc and co-workers have developed primaquine-CA conjugates of the amide (16) and acylsemicarbazide (17) type ( Figure 7) that generally presented middle to low micromolar activities against six cancer cell lines (L1210, CEM, HeLa, NCI-H460, SW 620, and MFC-7). The compounds were particularly active against the MFC-7 breast cancer cell line (0.03 < GI 50 < 16 µM), with four of the acylsemicarbazides 17 (Figure 7) displaying sub-micromolar activity against these cells.…”
Section: Repurposing Antimalarials For Cancer Via Conjugation To Cinnmentioning
confidence: 99%
See 1 more Smart Citation
“…Zorc and co-workers have developed primaquine-CA conjugates of the amide (16) and acylsemicarbazide (17) type ( Figure 7) that generally presented middle to low micromolar activities against six cancer cell lines (L1210, CEM, HeLa, NCI-H460, SW 620, and MFC-7). The compounds were particularly active against the MFC-7 breast cancer cell line (0.03 < GI 50 < 16 µM), with four of the acylsemicarbazides 17 (Figure 7) displaying sub-micromolar activity against these cells.…”
Section: Repurposing Antimalarials For Cancer Via Conjugation To Cinnmentioning
confidence: 99%
“…These acids are frequently found in a conjugated form, constituting key building blocks of complex polyphenols, such as acylated derivatives of flavonoid glycosides [5], and they have a number of biological roles in plants, from protection against microbes long been explored for their potential therapeutic applications, most of which related to their antioxidant, antimicrobial, and antineoplastic properties [4,[7][8][9][10][11][12][13][14]. The potential of CA-based compounds as therapeutic agents for other conditions, including Alzheimer's Disease [15], other nervous system disorders [16,17], acute pain [18], inflammation [19], diabetes [20,21], viral infections [22], tuberculosis [23][24][25][26], and malaria [26][27][28][29], among others, has also been addressed. Depending on their therapeutic targets, different modes of action seem to be exerted by CA and their derivatives or analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Za izražavanje akutne toksičnosti se koristi koncentracija jedinjenja koja dovodi do imobilizacije 50% jedinki populacije izložene njegovom dejstvu tokom unapred definisanog vremenskog perioda (najčešće 48h) i označava se kao efektivna koncentracija, EC50 [17]. Imajući u vidu da amidi predstavljaju veliku i raznovrsnu grupu biološki aktivnih molekula sa širokom primenom u medicini [18][19][20][21][22][23], poljoprivredi [24][25][26] i biotehnologiji [27,28] u ovom radu je proučavano hromatografsko ponašanje i lipofilnost odabranih derivata cijanoacetamida, primenom tankoslojne hromatografije na obrnutim fazama u smeši vode i tri organska modifikatora ponaosob (tbutanola, N,N,-dimetilformamida (DMF) i dimetilsulfoksida (DMSO)). Primenom metode linearne regresije je ispitana zavisnost između dobijenih hromato-grafskih parametara (RM0 i m) i softverski iz-računatih vrednosti podeonog koeficijenta, log P, kao i odabranih farmakokinetičkih prediktora, odnosno parametara toksičnosti proučavanih derivata cijanoacetamida.…”
Section: Uvodunclassified
“…On the other report, acetone extracts of rhizome and leaf of K. galanga including fractions were found to have a potent CNS depressant activity in the thiopental sodium-induced sleeping time, hole cross and open field models 2 . Several cinnamamides were proved to possessed sedative-hypnotic activity, but the structure-activity relationship of the sedative-hypnotic of the cinnamamides is unclear 23 . Searching of the literature indicated that there is no any publication reported about the sedative-hypnotic activity of compound 2.…”
Section: Introductionmentioning
confidence: 99%